Serviços ecossistêmicos hídricos na mata atlântica do sudeste brasileiro em cenários de conversão de uso e cobertura do solo e de mudanças climáticas - Santos, Paula Ferreira dos (2019)
While the role of land-use conversion on water quality is reasonably understood, its role on water quantity is controversial. Climate change is also expected to impact water availability. This work presents insights on the role of forests in the provision of hydrological ecosystem services concerning water quantity and quality. We then explore the interplay of the impacts of land-use and climate changes on water-related ecosystem services in Tietê Basin, Brazil, using scenario modelling. Our results corroborate the general trend that increased forest cover improves water quality. Our modelling also predicts that increased forest cover increases water quantity in the southern portion of the basin. The effects of climate change are felt mainly in urban areas, with a reduction in water quality. The trade-off between the improvements in water quality and quantity represent the greatest benefit of reforestation as a strategy to improve water availability in the region. We finish by discussing policy aspects of these stressors.